SCHOOL AS A HEALTH PROMOTING PLACE FOR ITS STUDENTS - Andre Guirland Vieira; Denise Rangel Ganzo de Castro Aerts; Sheila Câmara; Claudio Schubert; Dóris Cristina Gedrat; Gehysa Guimarães Alves (Universidade Estadual Paulista Júlio de Mesquita Filho, 2017)
The school has a strong commitment with the surrounding community as a space for the development of health promoting actions. However, for this space to be truly potentiating the quality of life, people should feel they are accepted and to participate in the process of building this healthy environment. So the aim of this study is to reflect upon the school as a health production space, and the importance of the health promoting school proposal.  For this purpose we conducted a theoretical research on school environment, social inclusion and health promotion in school facilities. Results point to the necessity for school to contribute for the development of healthy life abilities, reflecting upon life styles and promoting a healthy atmosphere for learning, which is appropriate for the student. That includes appraising individualities and establishing an atmosphere that potentiates healthy relations, with communication quality and with reflection upon diversities. It is specially found that teacher´s critical, creative and reflexive attitude plays an important role for healthy promoting school establishment, developing a pleasant, joyful and solidary environment, and stimulating joint search for doubts and questions.